Protective effect of gamma-tocopherol-enriched diet on N-methyl-N-nitrosourea-induced epithelial dysplasia in rat ventral prostate - Sanches, Lucas D.; Santos, Sergio A. A. [UNESP]; Carvalho, Jaqueline R. [UNESP]; Jeronimo, Gabriela D. M.; Favaro, Wagner J.; Reis, Maria D. G.; Felisbino, Sergio L. [UNESP]; Justulin, Luis A. [UNESP] (Wiley-Blackwell, 2013)
Despite recent advances in understanding the biological basis ofprostate cancer (PCa), the management of this disease remains a challenge. Chemoprotective agents have been usedto protect against or eradicateprostatemalignancies. Here, we investigated the protective effect of -tocopherol on N-methyl-N-nitrosourea (MNU)-induced epithelial dysplasia in the rat ventral prostate (VP). Thirty-two male Wistar rats were divided into four groups (n=8): control (CT): healthy control animals fed a standard diet; control+-tocopherol (CT+T): healthy control animals without intervention fed a -tocopherol-enriched diet (20mg/kg); N-methyl-N-nitrosourea (MNU): rats that received a single dose of MNU (30mg/kg) plus testosterone propionate (100mg/kg) and were fed a standard diet; and MNU+-tocopherol (MNU+T): rats that received the same treatment of MNU plus testosterone and were fed with a -tocopherol-enriched diet (20mg/kg). After 4months, the VPs were excised to evaluate morphology, cell proliferation and apoptosis, as well as cyclooxygenase-2 (Cox-2), glutathione-S-transferase-pi (GST-pi) and androgen receptor (AR) protein expression, and matrix metalloproteinase-9 (MMP-9) activity. An increase in the incidence of epithelial dysplasias, such as stratified epithelial hyperplasia and squamous metaplasia, in the MNU group was accompanied by augmented cell proliferation, GST-pi and Cox-2 immunoexpression and pro-MMP-9 activity. Stromal thickening and inflammatory foci were also observed. The administration of a -tocopherol-enriched diet significantly attenuated the adverse effects of MNU in the VP. The incidence of epithelial dysplasia decreased, along with the cell proliferation index, GST-pi and Cox-2 immunoexpression. The gelatinolytic activity of pro-MMP-9 returned to the levels observed for the CT group. These results suggest that -tocopherol acts as a protective agent against MNU-induced prostatic disorders in the rat ventral prostate.
Keywords: cell proliferation; epithelial dysplasia; MMP-9; N-methyl-N-nitrosourea; ventral prostate; gamma-tocopherol